The Impact of Engineering Design Process in Teaching and Learning to Enhance Studentsâ€™ Science Problem-Solving Skills (Jurnal Pendidikan IPA Indonesia, 2018)
This study aimed to determine the impact of the integration of engineering design process (asking, imagining, planning, creating and improving) in an electrical magnetism module to improve problem-solving skills in physics among secondary school students in Aceh, Indonesia. The quasi-experimental study was carried out with 82 form three (age 15 years old) students of a secondary school in Aceh Besar, Indonesia. The first author had randomly chosen two classes as the experimental group and two other classes as the control group. Independent samples t-test analysis was conducted to determine the difference between the physics teaching and learning module which integrated the five steps of engineering design process and the existing commonly used science â€œPudakâ€ teaching and learning module. The results of the independent samples t-test analysis showed that the use of the physics teaching and learning module which integrated the five steps of engineering design process was more effective compared to the use of the existing â€œPudakâ€ module in increasing the studentsâ€™ skills in solving physics problems. The findings of the study suggest that the science learning approach is appropriate to be applied in the teaching and learning of science to enhance science problem-solving skills among secondary school students. In addition, it can be used as a guide for teachers on how to implement the integration of the five steps of engineering design process in science teaching and learning practices.